Afro-Swedish and Ojibwe-Canadian Trauma Life Writings: Storms from Paradise, Reasons for Walking, and the Opening of Planetary Circles of Conversation - Egerer, Juliane (Scandinavian-Canadian Studies / Études scandinaves au Canada)

(untitled) (Association for the Advancement of Scandinavian Studies in Canada, 2023)
Following Spivak’s model of “crossing borders” and “planetarity”, this article compares two trauma life writings: Wab Kinew’s The Reason You Walk and Johannes Anyuru’s En storm kom från paradiset [A Storm Blew in from Paradise]. They negotiate transcultural identity construction and the intergenerational impact of colonialism, drawing respectively on Jewish philosophy of history, decolonization theory, and Indigenous Anishinaabe and Blackfoot worldviews. Deconstructing Eurowestern linear thinking, they reflect on the power of the moment and ongoing relational reciprocity. In this way, they embrace equity, diversity, and inclusion, and encourage planetary, transcultural, and decolonizing circles of conversation.